Rubella outbreak in the union territory of Chandigarh, North India. Issue 2 (25th August 2014) - Singh, Mini P.; Kumar, Archit; Gautam, Neha; Khurana, Jasmine; Gupta, Madhu; Ratho, Radha Kanta
ABSTRACT Rubella virus outbreaks usually occur when a large numbers of susceptible individuals accumulate. The disease presents clinically with fever and maculopapular rash. The present study reports the investigation of rubella outbreak in a modern and well‐planned village near Chandigarh, North India. The blood samples were collected from 39 cases with febrile rash and from 15 age and sex matched healthy controls residing in the same locality and subjected for the detection of Rubella IgM and IgG antibodies by Enzyme linked immunosorbent assay. The throat swabs, urine and blood samples from acute cases were also collected and subjected to RT‐PCR using the primers targeting the E1 region. The genetic characterization of the rubella virus was carried out to identify the circulating genotypes. In the present outbreak, 13 laboratory confirmed cases were reported. Rubella IgM antibodies were detected in 12/39 (30.7%) patients. Rubella RNA could be detected in 83.3% (5/6) of urine, 22.2% (2/9) of throat swabs, and 8.3% (1/12) of blood samples. The rubella genotype responsible for the present outbreak was identified as genotype 1a. This outbreak highlights the need for the introduction of rubella vaccine in the National Immunization Programme of India to prevent outbreaks and to aim towards the eradication of this disease. This study reports the presence of genotype 1a in North India for the first time and stresses the need for further molecular work to identify the circulating strains of the virus. J. Med. Virol. 87:344–349, 2015. © 2014 Wiley Periodicals, Inc.